C-D2-04: Persistence With Statins and All-Cause Mortality: A Population-based Cohort Study - Shalev, Varda (Marshfield Clinic, 2010)
Background: The beneficial effects of statins in secondary-prevention on cardiovascular mortality have been established in several long-term placebo-controlled trials; however, the value of statin therapy in reducing overall mortality in patients without coronary heart disease (CHD) is questionable. The study objective was to evaluate the effect of statin therapy in an unselected cohort of subjects with no indication of a cardiovascular-disease (primary-prevention) and patients with known CHD (secondary-prevention). Methods: Retrospective cohort study including 229,918 adult HMO enrollees in Israel, who initiated statin treatment in 1998–2006 (mean age 57.6; 50.8% female), and were followed-up for a maximum of 9.5 years. Proportion of days covered (PDC) with statins was measured by the number of dispensed statin prescriptions during the interval between the date of the first statin and end of follow-up. Adjustments were made for baseline values of age, sex and other personal characteristics, chronic medical conditions and healthcare utilization. Results: During 4.02 and 4.98 years of mean follow-up, there were 4,259 and 8,906 deaths among primary prevention and secondary prevention cohorts, respectively. In both cohorts, high persistence with statins (PDC>90%) confers at least 45% reduction in risk of death compared to patients with a PDC of <10%. Stronger risk reduction was calculated among patients with baseline LDL of >190 mg/dl and patients initially treated with high-efficacy statins. Conclusion: Better persistence with statin treatment provided an ongoing reduction in mortality among patients with and without known history of CHD. The observed benefits from statins were greater than expected from randomized clinical trials.